Evaluation of Chromogenic agar media for rapid identification of Candida species. - Nigar, Ismet; Tarafdar, Shirin; Khan, Rehana Razzak; Ahmed, S.M. Ali; Saleh, Ahmed Abu (Bangladesh Journal of Medical Microbiology, 2017)
Rapid identification of Candida isolates to the species level is essential in order to optimize the antifungal treatment. This study aimed to isolate and identify different species of Candida from various clinical specimens and to evaluate the use of chromogenic agar media as primary culture media for culture of Candida as well as for rapid identification of Candida species. A total of 100 different clinical specimens were studied (oral swab 35, high vaginal swab 28, catheterized urine 15, nail 14, bronchoalveolar lavage 04 and peritoneal fluid 04). Isolation of Candida species was done by primary culture in Sabouraud Dextrose Agar (SDA). Subsequent identification of species was performed by germ tube test, carbohydrate assimilation test (with commonly used twelve sugars) and subculture in chromogenic agar medium. Out of 64 isolated Candida, C. albicans 33 (51.53%) was the most predominant Candida species followed by C. tropicalis 17 (26.56%). The species of C. glabrata was 4 (6.25%), C. parapsilosis 4 (6.25%), C. krusei 3 (4.68%) and C.guilliermondii 2 (3.2%). One of the isolated Candida species was unidentified. The sensitivity and specificity of chromogenic agar media for C. albicans were as 96.97% and 96.87% respectively. The sensitivity and specificity for C. tropicalis were 94.12% and 97.87% respectively. C. krusei and C. glabrata both showed 100% sensitivity and specificity on chromogenic agar media. Efficacy of chromogenic agar media is nearly similar to carbohydrate assimilation method in species identification of Candida. Bangladesh J Med Microbiol 2015; 9 (1): 22-26